LEGAL PROTECTION OF VICTIMS OF COMMERCIAL SEXUAL EXPLOITATION OF CHILDREN THROUGH SOCIAL MEDIA - Samuel Libeltus Tamba; Hafrida; Herry Liyus (Universitas Bengkulu, 2024)
The crime of Commercial Sexual Exploitation of Children (ESKA) is increasingly rife with the existence of social media as a means of transaction and promotion of children who are victims. However, there is currently a vacuum in regulations that specifically regulate legal protection of the rights of children victims of these crimes. This study aims to describe the applicable rules in protecting children victims of CSEC through social media and how legal policies will be in the future in handling these crimes. The research method used is normative juridical research. From the results of the study, it was found that there is more than one legal regulation that is currently used to protect child victims of commercial sexual exploitation crimes through social media, namely the Child Protection Law, the Pornography Law, the Electronic Information and Transactions Law and the Sexual Violence Criminal Law. Some of the obstacles in protecting CSEC victims include: 1) legal substance factors (overlapping laws and regulations that specifically regulate CSEC crimes through social media), 2) legal structure factors (there is no legal umbrella for investigators and public prosecutors to be able to quickly break the chain of dissemination of cases of commercial sexual exploitation of children on social media; 3) legal cultural factors (public awareness, lack of parental monitoring, and lack of sexual education in children). The suggestions for future legal policies include: 1) Revising the Child Protection Law and the ITE Law; 2) strengthen the authority of the Prosecutor's Office and the Police as investigators and public prosecutors to remove social media content containing commercial sexual exploitation of children from the investigation and prosecution stages; 3) Create a child-friendly complaint and reporting center that is easily accessible to child victims of sexual exploitation crimes. Keywords: commercial sexual exploitation of children; social media; legal protection.